Comorbidity in multiple sclerosis is associated with diagnostic delays and increased mortality - Thormann, Anja; Sørensen, Per Soelberg; Koch-Henriksen, Nils; Laursen, Bjarne; Magyari, Melinda (Neurology, 2017)
To investigate the effect of chronic comorbidity on the time of diagnosis of multiple sclerosis (MS) and on mortality in MS. We conducted a population-based, nationwide cohort study including all incident MS cases in Denmark with first MS symptom between 1980 and 2005. To investigate the time of diagnosis, we compared individuals with and without chronic comorbidity using multinomial logistic regression. To investigate mortality, we used Cox regression with time-dependent covariates, following study participants from clinical MS onset until endpoint (death) or to the end of the study, censuring at emigration. We identified 8,947 individuals with clinical onset of MS between 1980 and 2005. In the study of time of diagnosis, we found statistically significant odds ratios for longer diagnostic delays with cerebrovascular comorbidity (2.01 [1.44-2.80]; <0.0005), cardiovascular comorbidity (4.04 [2.78-5.87]; <0.0005), lung comorbidity (1.93 [1.42-2.62]; <0.0005), diabetes comorbidity (1.78 [1.04-3.06]; 0.035), and cancer comorbidity (2.10 [1.20-3.67]; 0.009). In the mortality study, we found higher hazard ratios with psychiatric comorbidity (2.42 [1.67-3.01]; <0.0005), cerebrovascular comorbidity (2.47 [2.05-2.79]; <0.0005), cardiovascular comorbidity (1.68 [1.39-2.03]; <0.0005), lung comorbidity (1.23 [1.01-1.50]; 0.036), diabetes comorbidity (1.39 [1.05-1.85]; 0.021), cancer comorbidity (3.51 [2.94-4.19]; <0.0005), and Parkinson disease comorbidity (2.85 [1.34-6.06]; 0.007). An increased awareness of both the necessity of neurologic evaluation of new neurologic symptoms in persons with preexisting chronic disease and of optimum treatment of comorbidity in MS is critical.